Teacher Attrition: Differences in Stakeholder Perceptions of Teacher Work Conditions - Scott P. Harris; Randall S. Davies; Steven S. Christensen; Joseph Hanks; Bryan Bowles (MDPI AG, 2019)
The purpose of this study was to identify differences in perceptions between three stakeholder groups-principals, K-12 teachers, and parents-regarding the effect of workplace conditions on teacher attrition. All three groups agreed that workplace conditions are important, but they disagreed about (a) which workplace conditions are most problematic for teachers, (b) the magnitude of these problems, and (c) the degree to which these problems may contribute to teachers leaving. The greatest disagreements occurred in perceptions of (a) teachers' involvement in decision-making, (b) protection of teacher preparation time, (c) administration's management of student discipline, (d) adequacy of resource availability, (e) the degree to which a trusting and supportive school environment existed within the school, and (f) whether teachers' expectations were reasonable. Overall, principals believed that work conditions are relatively good for teachers, while many teachers disagreed with these perceptions.